Human Governance: Accessibility to Persons with Disabilities Sidorajo Regency - Dandi Darmadi; Gita Rania; Aulia Regita Dewi Fitriana; Ardian Bagus Setiawan (Future Science, 2021)
The consideration in this article clarifies the openness of people with disabilities in Sidoarjo Rule to different perspectives of life, not as it was related to physical offices and foundation but to get to social exercises utilizing the concept of Human Administration which has not been found in numerous comprehensive considers. People with incapacities are those who have physical limitations, so they have trouble altering their exercises in common. Essentially, people with incapacities moreover have the same rights and commitments as citizens. In any case, the get to of people with inabilities to physical and non-physical offices and foundation in Sidoarjo Rule is still considered not accessible appropriately. The approach used in this research is qualitative, sourced from primary data and secondary data. Data collection techniques are interviews, observation, and literature study. The results of research using the concept of Human Governance are found from the seven principles of Human Governance, which have not been fully implemented by the Sidoarjo regency government, especially those related to social accountability, education for citizens and reliability. There are still many Disability Associations in Sidoarjo Regency who do not attend school, especially formal schools, besides that the facilities and infrastructure such as those at SMAN 4 Sidoarjo are not disability friendly. Meanwhile, from the aspect of reliability, although the Sidoarjo regency government has been more serious in providing accessibility for persons with disabilities, the quality is still very low, such as the People Pedestrian Bridge (JPO) that is damaged, sidewalks in some locations are damaged and used for trading.